E-learning in business education : facing the challenge of the 21st century - Ann, Mia Choon (2008)
The increasing global prevalence of e-education has prompted critics to question the true value of a technology-enabled learning environment. The objective of this paper is to discuss the developments of e-learning thus far, as well as pinpoint factors that facilitate effective online learning for business courses in tertiary institutions.